THE INFLUENCE OF BASE PLUS LEAF FERTILIZATION ON PEACH QUALITY CULTIVAR ‘MACIEL’ - GAZOLLA NETO, Alexandre; GIACOBBO, Clevison Luiz; PAZZIN, Dalcionei; FACHINELLO, José Carlos (Scientia Agraria, 2007)
The present research aimed to evaluate base plus leaf fertilization on pre and post-harvest quality and productivity of peaches cultivar ‘Maciel’. The work was carried out in Pelotas/Brazil, 2005/06 crop. The tree planting density was at 1667 trees/ha in “Y” system. No irrigation method was used. The treatments consisted of 2 batches. The first one was applied on 26/08/2005 and 26/09/2005 and consisted of base fertilization containing 15.5% nitrate + 19% calcium + 0.3% boron, and leaf fertilization containing 0.5% of Kristasol® (12%N + 45%K2O + 1,2%S (nitric nitrogen and soluble non-chloride Potassium)). The second batch was applied on 20/10/2005 and 20/11/2005 consisting of 12% nitrate + 12% potassium + 15% soluble calcium + 0.24% boron (12-00-12 and 10-00-15 fertilization ratio, respectively) for base fertilization and 0.5% of the formulation containing 15.5% nitrogen + 19% soluble calcium for leaf fertilization. The base and leaf fertilization applied for each treatment were: 1) no fertilization (control); 2) 45 g tree-1; 3) 90 g tree-1; 4) 135 g tree-1 and 5) 180 g tree-1. The variables assessed were pulp firmness, total soluble solids (SST), colorimeter, fresh and dry matter of fruits, average fruit weight, yield rates, commercial ranking and decay incidence at the time of harvest and storage. The described fertilization rates did not show any improvement on fruit quality and productivity of the tested peach cultivar. The only variable that was found to be statically significant was fruit storage. Decay percentage was lower in fruits from treatments 1 and 2 at the 30th day of storage, being significant with respect to treatment 5. The others variables did not differ significatively.